Neurological congenital malformations in a tertiary hospital in south Brazil Malformações neurológicas congênitas observadas em hopsital terciário no sul do Brasil - Ana Guardiola; Vanessa Koltermann; Paula Musa Aguiar; Sérgio Pilla Grossi; Valéria Fleck; Elisabeth C. Pereira; Lúcia Pellanda (Arquivos de Neuro-Psiquiatria)
BACKGROUND: Congenital anomalies are one of the main causes of morbidity and mortality among infants. The involvement of the central nervous system (CNS) occurs in 21% of cases. OBJECTIVE: To identify incidence of CNS malformations and associated factors in newborns at a Terciary Hospital of Porto Alegre. METHOD: Case-control study conducted between 2000 and 2005 based on the Latin American Collaborative Study of Congenital Malformations database. RESULTS: Among 26,588 births registered in this period, 3.67% presented with malformations (IC=95%; 3.44-3.9), being 0.36% of the CNS (IC=95%,(0.29-0.43)). The most common CNS malformation was meningomielocele (10.4%). Young maternal age (p=0.005); low birth weight (p=0.015); large cephalic perimeter (p=0.003); post term birth (p=0.000) and low APGAR indexes at the 1st and 5th minutes were associated with CNS malformations. CONCLUSION: We found an incidence of CNS malformations similar as compared to literature. Anomalias congênitas são umas das principais causas de morbimortalidade infantil. O sistema nervoso central (SNC) é acometido em 21% dos casos. OBJETIVO: Identificar a incidência e fatores associados a malformações do SNC em recém nascidos na maternidade de um hospital terciário de Porto Alegre. MÉTODO: Estudo controle realizado de janeiro de 2000 a dezembro de 2005, baseado no banco de dados do Estudo Colaborativo Latino Americano de Malformações Congênitas. RESULTADOS: Dos 26.588 nascimentos, 3,67% apresentaram malformação (IC=95%; 3,44-3,9), com 0,36% do SNC (IC=95%, (0,29-0,43)). A malformação do SNC mais comum foi hidrocefalia (10,9%). Menor idade materna (p=0,005); menor peso ao nascimento (p=0,015), maior perímetro cefálico (p=0,003); nascimentos pré-termo (p=0,000) e menores índice APGAR no 1º e 5º minutos (p<0,000) apresentaram associação com malformações do SNC. CONCLUSÃO: Foi encontrada incidência similar de malformações do SNC comparada à literatura.